Silicon‐Based Photonic Architectures from Hierarchically Porous Carbon Opals. (19th November 2019) - Gil‐Herrera, Luz Karime; Gallego‐Gómez, Francisco; Torres‐Pardo, Almudena; González‐Calbet, Jose M.; Palomares, Francisco J.; Blanco, Alvaro; Juárez, Beatriz H.; López, Cefe
Abstract: Silicon‐based materials are needed in cutting‐edge technological fields, for which hierarchical porosity and photonic properties help improve performance. In this work, the versatility of several fabrication routes that combine silicon infiltration by chemical vapor deposition (CVD), reactive ion etching (RIE), and carbon calcination, which produce a palette of novel silicon‐based material architectures, is demonstrated. Design strategies are discussed and the main features of the processing steps are addressed to provide a variety of new silicon‐based materials with high morphological versatility and photonic quality. Three‐dimensional hollow carbon opals (HCO) permit control of the porosity of subsequent architectures through the initial silicon infiltration, while open or closed surfaces are achieved primarily as a function of RIE conditions. The composition of derived structures depends on the sequence in which the processes are applied. As a result, pure Si and hybrid C–Si inverse structures can be produced with open or closed spheres in the top layer and with an optional passivation layer. Remarkably, by properly choosing the Si infiltration parameters and the calcination/RIE procedure, final structures are achieved with double‐shell spheres. Abstract : By combining silicon chemical vapor deposition (CVD), reactive ion etching (RIE), and calcination, a host of versatile structures can be obtained from carbon sphere templates. The degree of infiltration, order and intensity of the processing steps, and characteristics of the initial porous, hollow spheres determines the final product. Among other functionalities, optical properties are favored by the regularity of the template.